Postnatal TrkB ablation in corticolimbic interneurons induces social dominance in male mice - Chen, Albert I-Ming (2019)
Our ability to reason, feel, and socialize relies on the development of a tight balance between inhibition and excitation within cortical circuits. The growth factor BDNF and its receptor TrkB are important for inhibitory neuron development and have been implicated in neuropsychiatric disorders. However, the behavioral consequences of impaired BDNF/TrkB signaling are unknown. Using a transgenic mouse line, we show that mice with deletion of BDNF/TrkB signaling from cortical inhibitory neurons exhibit social dominance and decreased inhibition within the prefrontal cortex, a key region regulating social behavior. Reversal of the network imbalance with optogenetic inhibition could rescue the behavior. Our results reveal a previously uncharacterized role of growth factor signaling within cortical interneurons for the development of social cognition.